Narrative Mediation: Techniques and Method for Resolving Conflcts in Organizations: Techniques and Method for Resolving Conflcts in Organizations - Peña Sandoval, Harvey (DIXI, 2015)
Purpose: Ths article addresses the techniques and methods of narrative mediation as a conflct resolution mechanism in an organizational context. Description: To fulfil this objective, narrative mediation is fist defied, aftr which the suppositions underlying the narrative theory as applied to conflct are presented. Techniques for intervention in the narrative mediation are then described, the stages of a mediation are specifid and fially conclusions are stated. Point of view: Based on mediation as a method of the discipline of conflct resolution, which is in turn based on narrative theories of conflct and its resolution. Conclusion: Narrative mediation enables employees and offials of companies and entities to resolve their conflcts, so that the parties can create narratives of respect, collaboration and mutual recognition. Thre must be commitment by academia and organizations to develop narrative mediation in Colombia.